Respuesta :
Answer:
x= -8/3
Step-by-step explanation:
(x-6)-(x+2)=3x
step 1) remove parentheses
x-6-x-2=3x
step 2) combine like terms
-8=3x
step 3) solve for x by dividing by 3 on both sides
-8/3 = x
Answer:
See below
Step-by-step explanation:
Hi there!
We want to solve the following equation:
(x-6)-(x+2)=3x
In this equation, notice how in front of (x+2), there is a minus sign
It's the same as if the equation was:
(x-6) + -1(x+2)=3x
We'll need to distribute the -1 to both terms, x and 2
so:
-1(x+2)= -1*x + -1*2= -x + -2, or -x-2
As for the (x-6), we can just open up the parenthesis without doing anything.
So on the left side, it becomes:
x -6 -x -2 = 3x
Now we can combine like terms.
x and -x are like terms, while -6 and -2 are like terms
x and -x add up to equal 0, while -6 and -2 add up to equal -8
-8 = 3x
Now, we have 3x by itself, but remember we just want x, or 1x.
Dividing a number by itself will result in 1
So we can divide both sides by 3
*note: we shouldn't divide by 3x. When we divide by 3, the result is [tex]\frac{3x}{3}[/tex], which if we cancel out the 3 from the numerator and denominator, gets the same result as 1x. If we divided by 3x, we'd just be getting 1 on the right side, while we'd be getting [tex]-\frac{8}{3x}[/tex] on the left, which isn't what we want.
-8/3=x
Hope this helps!